"Pseudo-Circumscribed Palmar or Plantar Hypokeratosis (Pseudo-CPH)": a Histologic Pattern Secondary to Trauma; Further Characterization of a Known Entity. (May 2016) - Groysman, Tatyana; Baldassano, Marisa F.
Abstract : Abstract: Circumscribed palmar or plantar hypokeratosis (CPH) is defined clinically as well-circumscribed areas of erythematous eroded skin mostly over thenar or hypothenar eminences of the palms and less commonly soles. Histologically, lesions demonstrate a characteristic abrupt drop-off in the cornified layer leading to broad areas of hypokeratosis. In the original description in 2002, Perez et al favored these lesions to be a distinctive epidermal malformation. Since then, some reports implicate trauma; however, the exact etiology remains uncertain. The authors present 11 cases in which the histologic changes of CPH are present as an incidental finding that they favor to represent a reaction pattern to trauma. The changes of CPH overly traumatized neoplasms [ie, a poroma, squamous cell carcinoma (2), dermatofibroma], verruca vulgaris (3), inflammatory processes (lichen amyloid and granulomatous inflammation secondary to a ruptured infundibular cyst), and scar and fibrosing granulation tissue from previous procedures. Classic clinical findings of CPH are not present. The changes most commonly but not exclusively occur on acral skin (8/11), both volar (4) and dorsal skin (4). Six patients are female and 5 are male. Ages range from 21 to 87 years (median 64 years). The authors propose that, in some instances, the histologic changes of CPH are present as a secondary phenomenon and represent a reaction pattern to trauma. They name this finding of secondary histologic change of CPH as "pseudo-CPH" to distinguish it from primary lesions of CPH ("primary CPH") with classic clinical and histologic features.